Analyzing the Presentation of Multilingual User Reviews in Accommodation Websites - da Rosa, Diego Moreira; Kuniechik, Natanael; Musse, Soraia Raupp; Silveira, Milene Selbach (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2021: Anais do XX Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2021)
Presenting user reviews in multiple languages is an increasingly common practice among system developers and can be found in the majority of accommodation websites nowadays. Despite this growth in popularity, the design strategies used to collect and present these multilingual reviews in a clear and useful way are yet to be uncovered. In order to understand how current accommodation websites are presenting the reviews of their international users, we assessed four popular systems applying the Semiotic Inspection Method. Results and triangulation with a previous study show that the design strategies still present some discrepancies and communicability problems, but slowly start to converge to a common set of patterns. We hope the results can help to identify a pattern language and good practices for the design aimed at bilingual and plurilingual users.